2022
DOI: 10.3390/ijms23020832
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of Epigenetically-Enhanced Extracellular Vesicles from a GelMA/Nanoclay Composite Hydrogel to Promote Bone Repair

Abstract: Extracellular vesicles (EVs) have garnered growing attention as promising acellular tools for bone repair. Although EVs’ potential for bone regeneration has been shown, issues associated with their therapeutic potency and short half-life in vivo hinders their clinical utility. Epigenetic reprogramming with the histone deacetylase inhibitor Trichostatin A (TSA) has been reported to promote the osteoinductive potency of osteoblast-derived EVs. Gelatin methacryloyl (GelMA) hydrogels functionalised with the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 86 publications
(123 reference statements)
1
43
0
Order By: Relevance
“…Importantly, we demonstrated that the EV-functionalised composite gels significantly enhanced hBMSCs osteogenic differentiation and mineralisation when compared to the EV-free groups, consistent with observations in the literature ( Man et al, 2021b ). Similar to the effects on proliferation, our findings showed an EV dose-dependent increase in mineralisation within the hydrogel, consistent with the concentration-dependent increase in hBMSCs mineralisation observed within a GelMA nanocomposite hydrogel ( Man et al, 2022 ). These findings further signify the efficacy of encapsulated EVs in stimulating hBMSCs osteogenesis within this hydrogel system.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Importantly, we demonstrated that the EV-functionalised composite gels significantly enhanced hBMSCs osteogenic differentiation and mineralisation when compared to the EV-free groups, consistent with observations in the literature ( Man et al, 2021b ). Similar to the effects on proliferation, our findings showed an EV dose-dependent increase in mineralisation within the hydrogel, consistent with the concentration-dependent increase in hBMSCs mineralisation observed within a GelMA nanocomposite hydrogel ( Man et al, 2022 ). These findings further signify the efficacy of encapsulated EVs in stimulating hBMSCs osteogenesis within this hydrogel system.…”
Section: Discussionsupporting
confidence: 86%
“…At day 1, 3, 5, and 7, the receiving medium was collected, and replaced by an equal volume of fresh PBS. Previous studies have shown that EVs derived from mineralising osteoblasts were CD63 positive and as such we selected this marker for the release study ( Man et al, 2021b ; Man et al, 2022 ). The EV concentration in the collected medium was evaluated using the CD63 ExoELISA-ULTRA complete kit (System Biosciences, United States) following the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, there is growing precedence for controlling the delivery of MSCs in situ to maximise their therapeutic efficacy. GelMA hydrogels have demonstrated their potential for different tissue engineering applications due to their plethora of desirable properties [ 34 , 38 , 39 ]. Hence, this study aimed to evaluate the capability of GelMA hydrogels reinforced with a 3D printed structural scaffold to support the MI192-induced mineralisation of hBMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were centrifuged at 10,000× g for 10 min at 4 °C, and lysates were collected for ALPSA assay. ALPSA quantification was determined using the 4-nitrophenyl colorimetric phosphate liquid system (pNPP, Sigma-Aldrich, Gillingham, UK) as previously described [ 15 , 34 ]. ALPSA was determined by normalisation with the total DNA content of the same sample.…”
Section: Methodsmentioning
confidence: 99%
“…Among the various counterparts used in the preparation strategy, nanoparticles such as nanoclays hold a certain importance [ 15 , 16 ]. Halloysite nanotubes (HNTs) are naturally occurring aluminosilicates possessing a hollow tubular shape in the nanometric scale and opposite charges between the external surface, which is negative, and the internal surface, which is positive [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%